Implementasi Kebijakan Aplikasi Zona Potensi Penangkapan Ikan di Kota Manado - Muluwere, Vrenky; Pratiknjo, Heny Maria; Purwanto, Anthonius (JURNAL ADMINISTRASI PUBLIK, 2021)
ABSTRACT Policy implementation is basically a way to achieve the objectives of the policy that has been made. Implementation is a significant stage in the public policy process because every policy must be implemented in order to have an impact in accordance with the policy objectives. This research was conducted by analyzing the implementation of fishing potential zone application policy in Manado City. The type of research used is qualitative descriptive research. The focus of this research is the Implementation of Fishing Potential Zone Application Policy in Manado City by looking at policy implementation indicators through Charles O. Jones theory namely Organizing, Interpretation and Application. There were 11 informants. Data collection techniques through Observation, Interviews, and Literature Studies. Data analysis stage: data reduction, data display, verification and conclusion. Presentation of data in the form of tables, images and narration. The results of the research obtained are that ZPAN application is not integrated with the relevant agencies, namely the Department of Agriculture, Marine affairs and Fisheries of Manado City in program planning, application development to application management. Furthermore, ZPAN application does not have a feedback assessment feature for user users of the application as an indicator in measuring the success of ZPAN applications. The Cooperation Agreement between Manado City Government and LAPAN through Memorandum of Understanding (MoU) No. 01/SETDAKO/PKS/10/01/2017 does not regulate specifically on how ZPAN application works causing the provision of geo-partial data of fish position from LAPAN far outside North Sulawesi Province and cannot be reached by manado city fishermen, As for the inhibition of the implementation of ZPAN policy, namely the absence of socialization programs and the provision of computer devices and internet networks on the coast of Manado City, the purpose of ZPAN application to support the welfare of fishermen has not materialized. Keywords: Policy Implication, ZPAN Application, Fisherman